Sleep problems and recall memory in children with Down syndrome and typically developing controls. (January 2020) - Lukowski, Angela F.; Slonecker, Emily M.; Milojevich, Helen M.
Highlights: Parent-reported sleep problems did not differ for children with Down syndrome and their typically developing peers. Sleep problems moderated the effect of group on the forgetting of individual target actions and their order. For children with Down syndrome, increased forgetting was associated with greater parent-reported sleep problems. Abstract: Background: Research conducted with typically developing (TD) infants and children generally indicates that better habitual sleep and sleep after learning are related to enhanced memory. Less is known, however, about associations between sleep and recall memory in children with Down syndrome (DS). Aims: The present study was conducted to determine whether parent-reported sleep problems were differentially associated with encoding, 1-month delayed recall memory, and forgetting over time in children with DS and those who were TD. Methods and procedures: Ten children with DS (mean age = 33 months, 5 days) and 10 TD children (mean age = 21 months, 6 days) participated in a two-session study. At each session, recall memory was assessed using an elicited imitation paradigm. Immediate imitation was permitted at the first session as an index of encoding, and delayed recall was assessed 1 month later. In addition, parents provided demographic information and reported on child sleep problems. Outcomes and results: Although parents did not report more frequent sleep problems for children with DS relative to TD children, regression-based moderation analyses revealed that more frequent sleep problems were associated with increased forgetting of individual target actions and their order by children with DS. Evidence of moderation was not found when examining encoding or delayed recall. Conclusions and Implications: Although group differences were not found when considering parent-reported sleep problems, more frequent sleep problems were positively associated with increased forgetting by children with DS relative to those who were TD. Although future experimental work is needed to determine causality, these results suggest that improved sleep in children with DS might reduce forgetting, ultimately improving long-term recall memory.